Analisis Penerapan Program Pencegahan dan Pengendalian Infeksi di Klinik X Tahun 2025 - Novita Novita; Ahdun Trigono; Samingan Samingan (LPPM Universitas Respati Indonesia, 2026)
Healthcare-associated infections (HAIs) remain a global challenge affecting patient safety, healthcare quality, and costs[1]. Global HAIs prevalence is estimated at 3.5–12%, with higher rates in rate reported in developing countries (10.1%) compared to developed countries (7.6%)[2]. In Indonesia, a Perdalin Jaya survey conductes in hospitals in Jakarta reported high infection rates, including Surgical Site Infection (SSI) at 18.9% and pneumonia at 24.5% [3]. Surveillance at Clinic X (2024) also indicated SSI (2.94%) and phlebitis (1.96%, exceeding the national standard set by the Ministry of Health (≤1.5%). This study aimed to evaluate the implementation of the Infection Prevention and Control (IPC) program at Clinic X. A concurrent embedded mixed-method design was employed, involving 60 patients for quantitative analysis and in-depth interviews with healthcare workers and management qualitative insight. The results demonstrated that medical waste and management and the availability of facilities and infrastructure were significantly associated with IPC implementation. Medical waste management emerged as the most dominant factor (p=0.044; OR=3.667), while dressing changes, intravenous catheter insertion, and injection procedures were not significantly associated. Barriers to IPC implementation include limited facilities and suboptimal compiance among healthcare workes, whereas managerial support, standars operating procedures (SOPs), and adherence to personal protective equipment (PPE) served as enabling factors. In conclusion, effective IPC implementation requires strengthning clinic policies in accordance with Ministy of Health Regulation No. 27/2017, improving medical waste management systems, and ensuring continious training and monitoring